Sleeper embedded insulated rail joints for minimising the number of modes of failure. (June 2017) - Zong, Nannan; Dhanasekar, Manicka
Abstract: Insulated rail joints (IRJs) identify broken rails and train locations in railway signalling circuitry, which are critical to the rail safety operation. Unfortunately, IRJs exhibit several failure modes due to complex interaction between their components, the load spectra and the support conditions. A novel idea of simplifying the design of the IRJs consisting of only two pieces of insulated rails embedded into a concrete sleeper in such a way that the free ends of the rails at the gap attain stiffness commensurate to that of the current designs where the gapped rails are connected with two joint bars (also known as fishplates) one on each side of the rail web with the assembly resting on top of sleepers. The advantages of the new design are that it exhibits stability levels comparable to the current designs with fewer components and hence fewer failure modes. A multi-objective optimisation framework was used for the development of the new design that enables safe passage of train wheels across the gap between the rails embedded in concrete sleepers. Feasibility of the sleeper embedded gapped insulated rails under traffic loading is demonstrated through a dynamic analysis of a rail wheel rolling on top of a selected optimal design from the Pareto front. The deformation components of the rail edge at the gap of the new design are shown to be lower than that of the classical insulated rail joints. Highlights: An innovative design of insulated rail embedded in concrete sleepers developed. The embedded insulated rail provides safe passage of wheels and aids signalling. Non-dominated sorting algorithm coupled with and parametric FE optimisation is proposed. Non-dominated solutions were obtained within 100 generations of genetic evolution. The deflection components of the optimal rail are shown lower than the current designs.